1962
DOI: 10.1083/jcb.15.2.335
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Structure of the Basement Membrane in Epidermal Tumors

Abstract: Epidermal tumors were induced in Swiss female mice by a topical application of 9, 10-dimethyl-l,2-benzanthracene solution followed by repeated applications of croton oil solutions. Fourteen benign and malignant tumors were sampled 25 weeks after the treatment had begun, fixed in osmium tetroxide or potassium permanganate, and embedded in Epon. Sections stained with lead hydroxide were examined. In three tumors defects of the epidermal basement membrane were seen. These defects accompanied local invasion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

1967
1967
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The most likely mechanism for the destruction at this junction still seems to be enzymatic, but the precise nature of this important alteration awaits elucidation. Pseudopodia have been described previously in premalignant and malignant lesions (Frei, 1962;Tarin, 1967;Frithiof, 1969;Woods & Smith, 1969Gould et al, 1975;White & Gohari, 1981b;Smith, 1981) and it has been suggested that they may have some role in the release of enzymes which may be responsible for the destruction of the underlying connective tissue. We have described the presence of small electrondense vacuoles which resemble lysosomal dense bodies (White & Gohari, 1981b;White et al, 1981) and these structures may provide the mechanism for these lytic processes.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely mechanism for the destruction at this junction still seems to be enzymatic, but the precise nature of this important alteration awaits elucidation. Pseudopodia have been described previously in premalignant and malignant lesions (Frei, 1962;Tarin, 1967;Frithiof, 1969;Woods & Smith, 1969Gould et al, 1975;White & Gohari, 1981b;Smith, 1981) and it has been suggested that they may have some role in the release of enzymes which may be responsible for the destruction of the underlying connective tissue. We have described the presence of small electrondense vacuoles which resemble lysosomal dense bodies (White & Gohari, 1981b;White et al, 1981) and these structures may provide the mechanism for these lytic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal bulging pseudopodia have been observed in vitro on human colon cancer cells (17) and on astrocytes that have been transformed by Rous sarcoma virus (25), but neither of these studies related the surface protrusions to the distribution of alpha filaments. In vivo, pseudopodial protrusions from the cancer cell surface have been observed in squamous cell carcinomas (9,18,42,46) and adenocarcinomas (14). These pseudopodia have often been considered as the earliest indication of malignant invasion (9,46).…”
Section: Discussionmentioning
confidence: 99%
“…Stoker (44) has reported that multiple pseudopodia appear on cells within 18 h after infection with a transforming virus. Pseudopodia also appear early in chemical carcinogenesis (18,49). However, pseudopod formation is not restricted to malignancy since other studies show that regenerating stratified squamous epithelia also have large pseudopodia (33,40,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1983. The mor phology of BMs in invasive carcinomas has been studied for more than sixty years [Broders, 1932;Frei, 1962;Vracko, I974;Abrahamson. I986: Van Den Hooff.…”
Section: Introductionmentioning
confidence: 99%